Adapting amidst adversity: investigating medical educators’ attitudes towards change and resilience in the face of educational barriers during COVID-19 pandemic - Khojasteh, Laleh; Karimian, Zahra; Nasiri, Elham; Kafipour, Reza (Frontiers in Education, 2025)
IntroductionResilience in the face of educational barriers refers to faculty members’ ability to effectively navigate, overcome, and adapt to challenges encountered in the educational environment. These challenges may include curriculum changes, transitions to online instruction, resource limitations, or disruptions caused by external factors, such as a pandemic. This study aims to explore the relationship between medical educators’ attitudes toward change and their resilience in overcoming these educational barriers.MethodsThis survey was conducted on 130 medical teachers of Shiraz University of Medical Sciences (SUMS) in 2021-2022. A standard questionnaire with 18 items was used to assess the teachers’ attitudes to change. A researcher-made questionnaire, including 36 items in eight components, was designed to assess the teachers’ resilience to educational barriers.ResultsBased on findings, teachers’ attitudes towards change were moderate in the affective and behavioral aspects but strongly positive in the cognitive aspect (p < 0.001). Teachers with more positive attitudes, compared to those with weaker attitudes, reported significantly fewer barriers in areas such as previous readiness (p = 0.025) and technical support (p = 0.005). Faculty members with better computer skills (p < 0.001) not only perceived fewer barriers but also exhibited more positive attitudes toward change (p = 0.002).ConclusionAttitudinal barriers are influenced by a person’s knowledge and skills, affecting their attitude toward change and willingness to face challenges. Involving teachers in diverse online education experiences and improving their competencies can enhance their acceptance of technological changes.